Indutor apoptótico de condensação da cromatina no núcleo: análise de genoma em plantas e perfil de expressão durante o estresse biótico em Vigna unguiculata [L.] Walp - Teixeira, Felipe de Castro (2022)
Apoptotic Inducer of Chromatin Condensation in the Nucleus (ACIN1) is a scaffold protein capable of interacting with RNA-binding proteins, such as RNA-binding Protein with serine-rich domain 1 (RNPS1) and Sin3A Associated Protein 18 (SAP18). ACIN1 was first described as a complex protein component responsible for triggering apoptosis in human cells. In plants, ACIN1 participates in silencing the Flowering C Locus (FLC), involved in vernalization in Arabidopsis, with no clear relationship to the plant MCP. Unlike in humans, there are no studies related ACIN1 to MCP in plants, as well as knowledge about the function of ACIN1 in plants is scarce. In the present study, we performed the analysis of the ACIN1 gene family in plants, paying special attention to the Fabaceae family, in view of a recent study reporting the differential expression of an ACIN1 protein during biotic stress. We identified 29 ACIN1 orthologs from 19 species belonging to 12 plant families. Phylogenetic relationships, physicochemical properties, gene structure, conserved motifs, cis-elements present in promoters, chromosomal localization, synteny regions and interaction network were investigated. Great conservation of ACIN1 protein domains was observed among plant families. The gene expression profile of the ACIN1 ortholog of Vigna unguiculata during biotic stress was verified, where differential expression was detected in both susceptible and resistant plants. Possible metacaspase cleavage sites were detected along the deduced amino acid sequences of ACIN1 proteins, showing the predicted homology between plant and human proteins. This study provides several insights into evolutionary, structural and functional features of the ACIN1 gene family in plants, predicting their participation in plant development and stress responses